Ionization electron signal processing in single phase LArTPCs: Part I Algorithm description and quantitative evaluation with MicroBooNE simulation - Adams, C; An, R; Anthony, J; Asaadi, J; Auger, M; Bagby, L; Balasubramanian, S; Baller, B; Barnes, C; Barr, G; Bass, M; Bay, F; et al. (IOP Science, 2018)
We describe the concept and procedure of drifted-charge extraction developed in the MicroBooNE experiment, a single-phase liquid argon time projection chamber (LArTPC). This technique converts the raw digitized TPC waveform to the number of ionization electrons passing through a wire plane at a given time. A robust recovery of the number of ionization electrons from both induction and collection anode wire planes will augment the 3D reconstruction, and is particularly important for tomographic reconstruction algorithms. A number of building blocks of the overall procedure are described. The performance of the signal processing is quantitatively evaluated by comparing extracted charge with the true charge through a detailed TPC detector simulation taking into account position-dependent induced current inside a single wire region and across multiple wires. Some areas for further improvement of the performance of the charge extraction procedure are also discussed.